Trends in genitourinary cancer mortality in the United States: analysis of the CDC-WONDER database 1999–2020 - Ghazwani, Yahia; Alghafees, Mohammad; Suheb, Mahammed Khan; Shafqat, Areez; Sabbah, Belal Nedal; Arabi, Tarek Ziad; Razak, Adhil; Sabbah, Ahmad Nedal; Alaswad, Marwan; AlKattan, Wael; Ouban, Abderrahman; Abdul Rab, Saleha; et al. (Frontiers in Public Health, 2024)
The literature on sociodemographic disparities of genitourinary cancer-related mortality is limited and focuses on single cancer types. We aimed to determine gender, racial, and geographic disparities in mortality for the most common genitourinary cancers in the USA. We obtained mortality data for the most common genitourinary cancers (prostate, bladder, kidney and testicular) from the Centers for Disease Control and Prevention (CDC) WONDER database between 1999 and 2020. We depicted their age-adjusted mortality rates (AAMRs) by year, gender, race, urban-rural status, and geographic region with a significance level of p<0.05. Overall, AAMRs for prostate, bladder, and kidney cancer declined significantly, but testicular cancer-related mortality remained stable. AAMRs for bladder and kidney cancer were 3-4 times higher in males than females. Prostate cancer mortality was highest in black individuals/African Americans and started to increase after 2015. Bladder cancer mortality declined significantly in White individuals, Black individuals, African Americans, and Asians/Pacific Islanders but remained stable in American Indian/Alaska Natives. Kidney cancer-related mortality was highest in White individuals but declined significantly in other races. Testicular cancer mortality rose significantly in White individuals but remained stable in Black individuals and African Americans.Genitourinary cancer mortality decreased in metropolitan areas but either increased (bladder and testicular cancer) or remained stable (kidney cancer) in non-metropolitan areas. Prostate and kidney cancer mortality was highest in the Midwest, bladder cancer in the South, and testicular cancer in the West. In conclusion, significant sociodemographic disparities exist in the mortality trends of genitourinary cancers in the US.